The Use of Lumi Education Application in Improving Arabic Language Skills for Students at Man 2 Makassar - Fitrah, Nurul Wasilah; Amin, Nurtaqwa; Ismail, Usman; Kurnia, Ulfa; Iman, Muhammad Zul (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2025)
This study aims to describe and analyze the use of the Lumi Education application in enhancing Arabic language skills among students of MAN 2 Makassar City. Employing a descriptive qualitative method, this research involved 37 students from class X.I as the sample. Data were collected through observation, interviews, questionnaires, and documentation during the Arabic learning process using the Lumi application. The findings reveal that the application had a positive impact on students' speaking abilities, motivation, participation, and comprehension. A total of 70.3% of students reported that the app was helpful and easy to use. Furthermore, 59.5% found it accessible and interactive, supporting their language learning. These results suggest that the Lumi Education application is an effective learning medium for improving Arabic language proficiency.